Coverage path planning on multi-depot, fuel constraint UAV missions for smart farm monitoring - De Ocampo, Anton Louise P. (Animo Repository, 2018)
UAVs used in monitoring crop fields are flying higher than 6 meters and capture telemetric data that provides information on the general condition of the plants in the field. But, in order to obtain specific information on the actual conditions of the plants based on individual morphological aspects, lower altitude monitoring, at most 3 meters, is required. Low-altitude missions cover less than high-altitude and requires UAVs to fly longer to cover more area. In this paper, an approach for multi-depot, fuel constrained coverage path planning is presented. First, target coverage is segmented into smaller regions based on the number of available charging depots. Then, each region is further decomposed into multitude of cells with area equivalent to the camera FOV when UAV is flying at 3 meters above the field. All possible routes are generated and fed into evolutionary optimization in aim to identify the optimal path considering the fuel constraints and availability of recharging depots. The optimization yields a significant improvement in obtaining the route that will provide the minimum distance that the UAV should traverse to cover the entire Area-of-Interest. This approach proved to be useful for crop field monitoring using UAVs. © 2018 IEEE.